Implementasi Pengembangan Pemikiran Siswa SMP Terhadap Kenakalan Remaja di SMPN 2 Trowulan Kabupaten Mojokerto - Anya Citra Kurnia Nanda; Cahya Rafiyoga Harnan; Excel Mulia Putrajaya Hartono; Faizah Radinka Karimah; Farrel Rakha Adi Pramana; Miftakhul Jannah; Rafi Eko Bachtiar; Rindyi Putri Lestari; Syarifuddin Aryasatya Nugraha (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Juvenile delinquency is a concerning phenomenon characterized by deviant behaviors that violate social norms and laws. This study aims to address the issue of juvenile delinquency in Bejijong Village, Trowulan District, Mojokerto Regency, through a socialization program targeted at middle school students. The program was designed to enhance the awareness and understanding of students at SMP Negeri 2 Trowulan regarding the negative impacts of juvenile delinquency. The methods used included seminars, educational videos, and interactive discussions. The results indicated that the students responded with high enthusiasm, demonstrating an increased understanding and awareness of juvenile delinquency. Active participation in discussions suggested the effectiveness of the approach. This program successfully stimulated critical thinking among students about juvenile delinquency issues and is expected to serve as a model for similar socialization programs in the future.